A Simple in vivo Assay Using Amphipods for the Evaluation of Potential Biocompatible Metal-Organic Frameworks - Sifaoui, Ines; Pacheco-Fernández, Idaira; Piñero, José E.; Pino, Verónica; Lorenzo-Morales, Jacob (Frontiers in Bioengineering and Biotechnology, 2021)
In this study, the application of amphipods in vivo assays was evaluated. Hence, six different MOFs were synthesized and the in vitro and ex vivo cytotoxicity was first assessed using a colorimetric assay and a macrophage cell line. Obtained results were compared to validate the in vivo toxicity tests carried out using amphipods and increasing concentrations of the different MOFs. Amphipods do not require the need of ethics approval and also are less expensive to keep than conventional in vivo models, showing its potential as a fast and reliable platform in toxicity studies. Therefore, the developed in vivo model could be applied as a high-throughput toxicity screening method to evaluate the toxicity of numerous materials, chemicals and therapeutic agents among others.